Comparison of Hypothesis- and a Novel Hybrid Data/Hypothesis-Driven Method of Functional MR Imaging Analysis in Patients with Brain Gliomas - Caulo, M.; Esposito, R.; Mantini, D.; Briganti, C.; Sestieri, C.; Mattei, P.A.; Colosimo, C.; Romani, G.L.; Tartaro, A. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: An alternative technique, which is less influenced by tumor- and patient-related factors, is required to overcome the limits of GLM analysis of fMRI data in patients. The aim of this study was to statistically assess differences in the identification of language regions and hemispheric lateralization of language function between controls and patients as estimated by both the GLM and a novel combined ICA-GLM procedure. MATERIALS AND METHODS: We retrospectively evaluated 42 patients with pathologically confirmed brain gliomas of the left frontal and/or temporoparietal lobes and a control group of 14 age-matched healthy volunteers who underwent BOLD fMRI to lateralize language functions in the cerebral hemispheres. Data were processed by using a classic GLM and ICA-GLM. RESULTS: ICA-GLM demonstrated a higher sensitivity in detecting language activation, specifically in the left TPJ of patients. There were no significant differences between the GLM and ICA-GLM in controls; however, statistically significant differences were observed by using ICA-GLM for the LI in patients. For the computation of the LI, ICA-GLM was less influenced by the chosen statistical threshold compared with the GLM. CONCLUSIONS: We suggest the use of the ICA-GLM as a valid alternative to the classic GLM method for presurgical mapping in patients with brain tumors and to replicate the present results in a broader sample of patients. ACanterior commissureANOVAanalysis of varianceBOLDblood oxygen level–dependentfMRIfunctional MR imagingGLMgeneral linear modelICindependent componentICAindependent component analysisIFGinferior frontal gyrusLIlateralization indexMLImedian of the lateralization indexMPRAGEmagnetization-prepared rapid acquisition of gradient echoPCposterior commissureTPJtemporoparietal junctionVGtverb-generation taskWGtword-generation taskWHOWorld Health Organization